PENGARUH PIMPINAN TERHADAP PRESTASI KERJA PEGAWAI BAGIAN PEMERINTAHAN KABUPATEN KUTAI BARAT - ., Magdalena . (PREDIKSI, 2014)
ABSTRACTÂ The purpose of this study was to determine whether the positive effect against the leadership of the Working achievements of Government Employees Kutai Barat regency. To get the data the authors conducted the study.The results showed that leadership greatly affect the performance of the employee, in the sense that the factor of the performance of the employees of the Government of Kutai Barat regency from month to month or from year to year change increase. This was followed by a leaderÂ in this function as cause variable..To improve employee work performance is good, then the leader must consider the welfare of the employees so that the employees do their job as best as possible, so that the performance of the employee of the Government of Kutai Barat regency could be improved